FEASIBILITY STUDY THE LEVEL OF IMPORTANCE OF EMPLOYEE VALUE PROPOSITIONS (EVPS) AND FLEXIBLE WORK ARRANGEMENTS (FWAS) TOWARDS WORK-LIFE BALANCE (WLB) IN HONG KONG - Siu Miu Margaret Chui, (PEOPLE: International Journal of Social Sciences, 2025)
To effectively utilize people nowadays, it is essential to understand EVPs and consider FWAs to achieve a WLB. Retaining employees is key to business success, especially as WLB has become a significant priority for young employees. Organizations are exploring attractive EVPs and FWAs as HR strategies to attract, engage, and retain talents to address this. However, there is limited research on the specific needs and preferences of HK employees regarding these workplace offerings. This study aims to assess the importance of employees in various EVPs and FWAs in achieving a good WLB in HK. A quantitative approach is employed, targeting 200 white-collar employees in HK. 217 questionnaires were collected, 4 (1.84%) were invalid, and 213 (98.1%) data were deemed valid for analysis using statistical techniques such as descriptive analysis, crosstab, correlation, and factor analysis. Findings indicated that "WLB", "Pay and Benefits", and "Harmony Relationships" were the most significant EVPs. The preferred flexible working pattern is the "Hybrid Model", but surprisingly the second most common arrangement is "Normal Work Hours". Notably, "long working hours" were identified as the primary cause of WLB Imbalance, followed by a "Lack of Workplace Flexibility" and "Company Culture".To improve WLB, respondents emphasized the need for "Flexible Work Hours" and the second most common benefits are "Work from Home Policy" and "Company Culture". Besides, most respondents indicated they would consider quitting their jobs if WLB was not supported. WLB is important because of "Private Time for Myself", and the second is "Family Commitments".For the FWAs, the data showed that most respondents do not consider FWAs such as varied schedules, remote work, or self-directed work, is likely in HK. Respondents also indicated that FWAs increase both productivity and motivation. The results provide insights for organizations to develop effective EVPs and FWAs that meet employee needs. This is essential for improving WLB and enhancing employee attraction, engagement, and retention. The findings also guide policymakers and HR professionals in HK to support work-life balance initiatives, fostering a more productive work environment for employees and employers.